Condition monitoring of bearings using vibrations / Rasyidah Othman and Zuraidi Yusof - Othman, Rasyidah (1999)
The use of sophisticated machines has become essential to the highly technical industries. Cost of breakdown and maintenance for these machines becomes extremely prohibitive. Bearing is an important element in the operation of these machines. Therefore, to reduce the cost of maintaining the machine, the monitoring of the bearing condition is becoming increasingly important. This project. was mainly carried out to design the in-house test rig for conducting the bearing testing. Experiments have been conducted to establish _the 'baselines' that can be used for identifying the bearing faults. The monitoring of the bearing condition is done by using the FFT Dual Channel Portable Signal Analyzer Type2418 (Brilel & Kjaer). Chapter 1, introduces the need to monitor the bearings and why vibration measurement is used in monitoring. Also, it describes the objectives of this project. In Chapter 2, is the literature review about bearing; its applications and the instrumentation that need to take into considerations on conducting the testing. Chapter 3 gives an idea of the basic theory on condition monitoring such as vibration transducer, vibration testing, misalignment and fault detection in rotating machinery. Frequency spectrum and its relationship to condition monitoring and spectrum interpretation for the results is also given in this chapter. Design of the test rig, experimental procedures and program used are given in this chapter 4. This section also describes the experiments that were carried out and the procedures that need to be followed to achieve the objectives.